Facile laser fabrication of high quality graphene-based microsupercapacitors with large capacitance. (October 2018) - Kwon, Soongeun; Yoon, Yeoheung; Ahn, Junhyoung; Lim, Hyungjun; Kim, Geehong; Kim, Jae-Hyun; Choi, Kee-Bong; Lee, JaeJong
Abstract: We have demonstrated facile laser fabrication of high quality graphene-based microsupercapacitors (MSCs) by carbon dioxide (CO2 ) laser-assisted reduction and successive ultraviolet (UV) pulsed laser direct carving of a graphene oxide (GO) film. Irradiation of GO films by a high power CO2 laser generated high quality laser reduced graphene oxide (LrGO) films with fewer defects (ID /IG  = 0.24) and excellent expansion ratio (∼16) suitable for a large capacitance electrode. UV laser direct carving was applied to fabricate a high resolution interdigitated electrode (IDE) pattern of an LrGO film (LrGO-IDE) with both the minimum electrode width and gap between the electrodes, being as small as 50 μm. A typical MSC based on the LrGO-IDE shows large areal specific capacitance of 32.6 mF cm −2 at a scan rate of 10 mV s −1 and 29.8 mF cm −2 at a current density of 0.2 mA cm −2, outperforming most rGO-based MSCs. Moreover, the electrochemical performance of the MSCs based on LrGO-IDEs is greatly improved by minimizing the electrode width in the same electrode footprint. High resolution IDE patterns composed of the high quality LrGOs developed here can be further applied for high power pseudo-capacitors by incorporating pseudo-capacitive materials into the porous LrGO structure. Graphical abstract: Image 1